Anaerobic Co-Digestion of Food Waste and Microalgae at Variable Mixing Ratios: Enhanced Performance, Kinetic Analysis, and Microbial Community Dynamics Investigation - Zhiyong Pan; Xuan Sun; Yali Huang; Tian Liang; Jilai Lu; Limin Zhang; Chuang Qi (Applied Sciences, 2024)
There is an urgent need for clean recycling strategies to address the increase in food waste (FW) and the harvesting of microalgae (MA). In this study, biogas production potential and operational stability were evaluated by testing combinations of FW and MA mixed at five different ratios. Co-digestion of FW and MA improved substrate biodegradability, achieving a decomposition rate of 0.45/d (FW/MA = 1:1), which is 1.25 to 1.55 times higher than that of MA or FW alone. Co-digestion of FW and MA resulted in a synergistic effect, improving biogas yield by 2.04–26.86%. Four mathematical models were applied to estimate biological degradation and biogas production kinetics, and the Cone model performed better than the other models in terms of reliability and accuracy. The abundance of Bacteroidetes, Firmicutes, and Synergistetes peaked at FW/MA = 1:1. At the same ratio, the genera Methanospirillum, Methanocorpusculum, and Methanomethylovorans were also found to have increased in abundance. The optimal ratio was found to be 1:1 for co-digestion of FW and MA, which is a feasible approach for simultaneous bioenergy production and biomass waste co-disposal.